Comparative Water Quality Assessment of Cascade Urban Lakes: Dori, Walini, and Dora in Bogor Regency, Indonesia - Rahmadya, Aldiano; Yusuf Afandi, Ahmad; Rohaningsih, Denalis; Novianti, Relita; Verawati, Dewi; Dianto, Aan (LIMNOTEK Perairan Darat Tropis di Indonesia, 2024)
Urban lakes are critical in flood mitigation, providing fresh water, and offering green spaces in urban environments. However, many urban lakes face increasing ecological pressures from various human activities. This study assesses the water quality and morphometric conditions of three urban lakes—Dori, Walini, and Dora in the Cibinong Botanical Garden Complex in Bogor Regency, located in a high-rise residential area. The study aims to evaluate the current water quality, identify contributing factors to water quality degradation, and compare conditions across the three lakes. Data was collected between January and April 2023, utilizing a Geographic Information System (GIS) for morphometric analysis and water quality measurements. Water quality was assessed in accordance with the standards set by Government Regulation No. 22 of 2021. Results indicate that Lake Dori, Walini, and Dora have surface areas of 3,406.96 m², 7,668.37 m², and 13,599 m², respectively. Based on water quality classifications, both Lake Walini and Lake Dori meet Class III standards (suitable for water use), while Lake Dora, though also in Class III, exhibits milder pollution indicators. These findings provide important insights for managing urban lakes and can guide future environmental policies.